2019
DOI: 10.1101/710277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chloride dynamics alter the input-output properties of neurons

Abstract: Fast synaptic inhibition is a critical determinant of neuronal output, with subcellular targeting of synaptic inhibition able to exert different transformations of the neuronal input-output function. At the receptor level, synaptic inhibition is primarily mediated by chloride-permeable Type A GABA receptors. Consequently, dynamics in the neuronal chloride concentration can alter the functional properties of inhibitory synapses. How differences in the spatial targeting of inhibitory synapses interact with intra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…relatively small increases in [Cl − ] i will depolarize E Cl toward V rest (Currin et al, 2020). This significantly reduces or even eliminates hyperpolarizing inhibition thus affecting the inputout function of neurons and modify or even degenerate neuronal function (Currin et al, 2020).…”
Section: Ionic Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…relatively small increases in [Cl − ] i will depolarize E Cl toward V rest (Currin et al, 2020). This significantly reduces or even eliminates hyperpolarizing inhibition thus affecting the inputout function of neurons and modify or even degenerate neuronal function (Currin et al, 2020).…”
Section: Ionic Plasticitymentioning
confidence: 99%
“…relatively small increases in [Cl − ] i will depolarize E Cl toward V rest (Currin et al, 2020). This significantly reduces or even eliminates hyperpolarizing inhibition thus affecting the inputout function of neurons and modify or even degenerate neuronal function (Currin et al, 2020). Computational models of a mature CA1 pyramidal neuron revealed that shifting the reversal potential of GABA (E GABA ) by only ∼2.5 mM (∼ to 5 mV from −75 to −70 mV) results in an increase in action potential firing by 39% (Saraga et al, 2008).…”
Section: Ionic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation